Pengaruh Temuan Audit, Tindak Lanjut Hasil Pemeriksaan, Serta Kinerja Keuangan Terhadap Tingkat Korupsi Pemerintah Daerah (Studi Empiris Pada Pemerintah Kabupaten dan Kota di Jawa Tengah Tahun 2020-2023) - Adelia Yona Rahmatika; Dwi Cahyo Utomo (Diponegoro Journal of Accounting, 2025)
This study aims to examine the effect of audit findings, follow-up of audit results, and financial performance on the level of corruption in local governments (an empirical study on regency and city governments in Central Java for the period 2020–2023). The independent variables in this research are audit findings, follow-up of audit results, and financial performance, while the dependent variable is the level of corruption.The study utilizes secondary data sourced from the audit reports of the Audit Board of the Republic of Indonesia for Central Java and corruption data from the Central Java High Prosecutor’s Office. The sampling technique used is purposive sampling, resulting in 140 observations from various regencies and cities in Central Java. The data were analyzed using multiple linear regression analysis.The results show that audit findings have a negative effect on the level of corruption. Follow-up of audit results shows a positive influence. Financial performance, measured by the independence ratio, has a negative effect on corruption. Financial performance based on the operational expenditure ratio has no significant effect. Meanwhile, financial performance based on the capital expenditure ratio has a negative impact.